Effects of the epiretinal membrane on the outcomes of intravitreal dexamethasone implantation for macular edema secondary to branch retinal vein occlusion - Altintas,Ayse Gul Kocak (2023)
ABSTRACT Purpose: To investigate the effects of epiretinal membrane formation on the clinical outcomes of intravitreal dexamethasone implantation for macular edema secondary to branch retinal vein occlusion. Methods: This retrospective interventional case series includes the treatment of naive patients with macular edema secondary to non-ischemic branch retinal vein occlusion who underwent intravitreal dexamethasone implantation. The patients were divided into two groups as follows: Group 1 (n=25), comprised of patients with macular edema secondary to branch retinal vein occlusion without epiretinal membrane, and Group 2 (n=16), comprised of patients with macular edema secondary to branch retinal vein occlusion with an epiretinal membrane. Corrected visual acuity, central macular thickness, and central macular volume values were measured before and after treatment. The clinical outcomes of the groups were compared. Results: Mean age and male-to-female ratio were similar between the two groups (p>0.05, for both). The baseline and final corrected visual acuity values, central macular thickness, and central macular volumes of the groups were similar (p>0.05, for all). All the parameters were significantly improved after intravitreal dexamethasone implantation treatment (p<0.001, for all). The changes in central macular thickness and volume were also similar (p>0.05, for both). The mean number of intravitreal dexamethasone implantations was 2.1 ± 1.0 (range, 1-4) in Group 1 and 3.0 ± 1.2 (range, 1-5) in Group 2 (p=0.043). Conclusion: Epiretinal membrane formation had no effects on the baseline and final clinical parameters, including corrected visual acuity and central macular thickness and volume. The only parameter affected by the presence of epiretinal membrane formation is the number of intravitreal dexamethasone implantations, a greater number of which is needed for macular edema secondary to branch retinal vein occlusion with an epiretinal membrane.